Symptom management in people dying with COVID-19: multinational observational study. Issue 4 (8th September 2022) - Oluyase, Adejoke Obirenjeyi; Bajwah, Sabrina; Sleeman, Katherine E; Walshe, Catherine; Preston, Nancy; Hocaoglu, Mevhibe; Bradshaw, Andy; Chambers, Rachel L; Murtagh, Fliss E M; Dunleavy, Lesley; Maddocks, Matthew; Fraser, Lorna K; et al.
Abstract : Objectives: To describe multinational prescribing practices by palliative care services for symptom management in patients dying with COVID-19 and the perceived effectiveness of medicines. Methods: We surveyed specialist palliative care services, contacted via relevant organisations between April and July 2020. Descriptive statistics for categorical variables were expressed as counts and percentages. Content analysis explored free text responses about symptom management in COVID-19. Medicines were classified using British National Formulary categories. Perceptions on effectiveness of medicines were grouped into five categories; effective, some, limited or unclear effectiveness, no effect. Results: 458 services responded; 277 UK, 85 rest of Europe, 95 rest of the world, 1 missing country. 358 services had managed patients with confirmed or suspected COVID-19. 289 services had protocols for symptom management in COVID-19. Services tended to prescribe medicines for symptom control comparable to medicines used in people without COVID-19; mainly opioids and benzodiazepines for breathlessness, benzodiazepines and antipsychotics for agitation, opioids and cough linctus for cough, paracetamol and non-steroidal anti-inflammatory drugs for fever, and opioids and paracetamol for pain. Medicines were considered to be mostly effective but varied by patient's condition, route of administration and dose. Conclusions: Services were largely consistent in prescribing for symptom management in people dying with COVID-19. Medicines used prior to COVID-19 were mostly considered effective in controlling common symptoms.